Modelo híbrido de apoio à decisão multicritério na manutenção preventiva de patrimônios culturais edificados de Sobral - Olimpio, Luiz Carlos Magalhães (2020)
When buildings are recognized for their historical and cultural representativeness, they can be classified as cultural built heritage. These heritage buildings must be preserved due its important tangible and intangible value, and because they are often vulnerable due their constructive solutions. In this regard, decision making involving interventions became complex, as it needs to consider not only aesthetic and structural characteristics, but also subjective ones. This research elaborates a hybrid model for multicriteria decision making in the maintenance comprised in a preventive conservation approach in built heritage in the historic center of the city of Sobral in Brazil. The model elicits expert knowledge of key areas for criteria weighting using a method that adopts the Bayes theorem (BBWM). The built historical heritage are evaluated in two stages: The first is the analysis of structural vulnerability considering the seismicity of the city of Sobral, carried out by the Structural Assessment and Rehabilitation Laboratory (LAREB), and modified for fuzzy variables. The second is the collection of decision makers' preferences. Finally, a prioritization method to group decisions is applied (FG- MULTIMOORA), resulting in a hierarchical ordering. Nine sub-criteria are assessed and comprised in three criteria named structural vulnerability, cultural significance, and potential and constraints. The weighting indicated the strong influence of social value in the definition of preventive maintenance policies, ahead of the facades, roofs and quality of construction materials. The results also indicate economic and regulatory constraints as the least important subcriterion. The hierarchy indicates the buildings that occupy the first positions to those that had a consensus in the assessment of decision makers. Among these are socio-cultural equipment and buildings that have obtained higher vulnerability indexes. This research contributes by presenting a robust and novel decision model for the maintenance of built historical heritage, considering multiple criteria aligned with the material heritage preservation charters and national listing studies, as well as important economic and social aspects for the city, promoting its sustainable development. The results are relevant by promoting an analytical and multidisciplinary recognition of the scenario, and by supporting a transparent and systematic decision-making process in the promotion of preventive strategies, policies and interventions in historical sites and heritage buildings